Analysis and simulation of the hysteretic behavior of reinforced concrete columns using multi-component rigid-body spring-discrete element method - Saguid, James Godfhrey L.; Tingatinga, Eric Augustus J.; Longalong, Romeo Eliezer U. (Quezon City College of Engineering, University of the Philippines Diliman, 2016)
The finite element method is the generally accepted method for linear elastic analysis of structures, but the required computational power for nonlinear analysis limits its applicability. Of the many developing methods for nonlinear analysis, the Rigid Body Spring - Discrete Element Method (RBS-DEM) is chosen as an alternative. RBSDEM uses rigid bodies connected by spring systems in which the displacements of the structure can be fully described by the motion of the rigid bodies, while the strain energy is stored in the springs. In this study, the governing equations of planar multicomponent RBS-DEM model of reinforced concrete columns were derived considering shear, axial and flexural capacities, and were applied to simulate the behavior of columns subjected to static loading. The columns were discretized into a finite number of rigid bodies, and the column capacities and energy dissipation mechanisms were approximated by nonlinear spring systems with hysteresis. The nonlinear spring parameters were derived from section properties by using Response 2000 and the spring restoring forces were calculated based on Takeda and Fukada hysteresis rules for the flexure springs, bilinear hysteresis for the shear springs, and elastoplastic rule for the axial springs. The differential equations of motion of columns subjected to cyclic loads were solved using a numerical timestepping method. Twelve columns were selected from the Pacific Earthquake Engineering Research Center (PEER) Structural Performance Database, to represent samples of shear-critical, shear-flexure-critical, and flexure-critical columns. It was concluded that the RBS-DEM model of columns was able to reasonably replicate the load-deformation characteristics of experimental columns. For shear-critical columns, a single-component model is enough to simulate the actual response. For flexure-critical and shear-flexure-critical columns, a multi-component model is recommended to better capture the flexibility of the column.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Columns, Concrete; Discrete element method